Brain connectivity for constructing new face representations in typical adults versus a prosopagnosic patient - Ela I. Olivares; Jorge F. Bosch-Bayard; Ana S. Urraca; Alba Jiménez-Bascuñán; Rolando J. Biscay; Jaime Iglesias (NeuroImage)
Will our brains get to know a new face better if we look at its external features first? Here we offer neurophysiological evidence of the relevance of external versus internal facial features for constructing new face representations, by contrasting successful face processing with a prototypical case of face agnosia. A woman with acquired prosopagnosia (E.C.) and 14 age-matched typical participants (7 women) were exposed to a face-feature matching task. External (E), internal (I) features, and whole target faces of unknown individuals (from an IdentiKit gallery) were displayed according to two different sequences: E →I→whole faces, or I→E→whole faces. Then, we studied the induced EEG activity using ‘isolated effective coherence’ to analyse the intracortical causal information flow among face-sensitive nodes. Initial presentation of external features (E before I), when compared to internal ones, triggered connections encompassing extensively the right-hemisphere face processing pathway [from posterior visual cortices for initial structural analysis, towards both intermediate (occipitotemporal) and high-level (prefrontal) relay stations], in which face-identity is thought to emerge progressively. Also, whereas exposure to internal features as second stimulus seemed to demand some sort of basic visual processing, external features triggered again more widespread and integrative connections. Connections for whole faces closing the E-I sequence resembled those for external features initiating the same sequence. Meanwhile, the predominant connections for whole faces completing the I-E sequence were more restricted to specific brain areas, with relevant prefrontal activity and a few connected nodes in right posterior regions, suggesting high attentional load plus initial and intermediate processing of face identity. Interestingly, the pattern of connections that distinguished typical participants from E.C. in the I-E sequence was the recruitment of left posterior visual regions, presumably underlying analytical subroutines for structural encoding of facial stimuli. These findings support that initial exposure to external features, followed by internal ones, provides the best visual cue to acquire new face configurations. Nevertheless, in case of face agnosia after right posterior damage, relying preferentially on internal features and left hemisphere specialized subroutines might be an alternative for cognitive training.